Shaking table test on suspend-dome structure with the center-hung scoreboard under three-dimensional seismic. (April 2023) - Lu, Zhen; Xue, Suduo; Li, Xiongyan; Liu, Renjie
Abstract: In order to meet the demand of watching games, the LED display, i.e., the center-hung scoreboard, has been widely used in large stadiums. To investigate the mechanical properties of the suspend-dome structure with the center-hung scoreboard under the action of earthquake, a dynamic scaled model with a geometric similarity ratio of 1:20 was designed. And the shaking table test was performed to study the seismic performance under the actions of 8 degree frequent, seismic precautionary and rare earthquakes. The acceleration, displacement and internal force responses under three-dimensional seismic were analyzed. The results show that the Z-directional acceleration amplification factors of the reticulated shell vertex region are significant and decrease fastest under actions of rare earthquakes, which is the weak point of the model. The influence of the center-hung scoreboard on the structure cannot be ignored in the study of seismic performance. The vertical displacement is the largest in the center and gradually decreases from inside to outside. The maximum displacement under actions of frequent earthquakes is 2.061 mm. The maximum displacement under actions of seismic precautionary earthquakes is 1/556, the maximum displacement under actions of rare earthquakes is 1/242, both of which satisfy the requirement of seismic specifications. The maximum internal force of the ring rod first decreases and then increases from the center to the surroundings. The internal force of the radial rod gradually increases from the edge to the center. Under actions of rare earthquakes, the center-hung scoreboard has more influence on the internal force of the rod. The accuracy of the finite element modeling method is verified by comparing the simulation results and test results of the scaled model, and the reliability of the scaled model is verified by comparing the simulation results of the scaled model and the prototype structure. The structure does not collapse under actions of 8 degree rare earthquakes and does not show apparent failure. The seismic principle that "the structure hasn't damaged under frequent earthquake, repairable under precautionary earthquake, and doesn't collapse under rare earthquake" is reached, thus the structural design of the Lanzhou Olympic Sports Complex is reasonable.